Gut Microbiome Dysbiosis Associated to Mental Health: Cognitive Functioning, Stress Resilience, Neuroticism and Quality of Life Affected by Gut-Brain Axis - Hafsa Mushtaq; Masooma Rasheed; Dr. Saad Hassan Khan; Aneeba Arif (Research Journal of Psychology, 2025)
In recent years, the association between the Gut Microbiome Dysbiosis and Mental Health have been the target of interest for many researches as it has proved to affect the Brain through a bidirectional pathway between the brain and gut known as Gut-Brain Axis. The focus of this study is to evaluate the effects of gut related diseases on cognitive functioning, stress resilience, neuroticism and quality-of-life among the patients of gut microbiome dysbiosis. For this purpose, quantitative research was conducted through correlation research design. A sample of 42 patients was selected by purposive sampling technique from different hospitals of Lahore. To measure the variables Cognition Self-Assessment Rating Scale, Brief Resilience Scale BRS, The Big Five Inventory’s Neuroticism Subscale and The World Health Organization’s scale WHOQOL-BREF were administered. The results indicate p= .073 for C-SARS, p= .008 for BRS and p< .001 for BFIN that revealed not a significant relationship between Quality-of-life QOL and cognitive functioning, significant but negative prediction between QOL and resilience, as well as a negative significant relationship between higher neuroticism and lower QOL. The study had unveiled the correlation between gut dysbiosis and its ramifications on psychological health of patients and how they are affecting quality of life of the individuals. These results will lead to a better understanding of association between gut microbiome dysbiosis and cognition, resilience, and neuroticism to improve their mental and physical health.